COMP Report: CPQR technical quality control guidelines for use of positron emission tomography/computed tomography in radiation treatment planning. Issue 12 (8th October 2022) - Klein, Ran; Oliver, Mike; La Russa, Dan; Agapito, John; Gaede, Stewart; Bissonnette, JeanPierre; Rahmim, Arman; Uribe, Carlos
Abstract: Positron emission tomography with x‐ray computed tomography (PET/CT) is increasingly being utilized for radiation treatment planning (RTP). Accurate delivery of RT therefore depends on quality PET/CT data. This study covers quality control (QC) procedures required for PET/CT for diagnostic imaging and incremental QC required for RTP. Based on a review of the literature, it compiles a list of recommended tests, performance frequencies, and tolerances, as well as references to documents detailing how to perform each test. The report was commissioned by the Canadian Organization of Medical Physicists as part of the Canadian Partnership for Quality Radiotherapy initiative.